Characterization of Apis mellifera Gastrointestinal Microbiota and Lactic Acid Bacteria for Honeybee Protection—A Review - Adriana Nowak; Daria Szczuka; Anna Górczyńska; Ilona Motyl; Dorota Kręgiel (Cells, 2021)
Numerous honeybee (Apis mellifera) products, such as honey, propolis, and bee venom, are used in traditional medicine to prevent illness and promote healing. Therefore, this insect has a huge impact on humans’ way of life and the environment. While the population of A. mellifera is large, there is concern that widespread commercialization of beekeeping, combined with environmental pollution and the action of bee pathogens, has caused significant problems for the health of honeybee populations. One of the strategies to preserve the welfare of honeybees is to better understand and protect their natural microbiota. This paper provides a unique overview of the latest research on the features and functioning of A. mellifera. Honeybee microbiome analysis focuses on both the function and numerous factors affecting it. In addition, we present the characteristics of lactic acid bacteria (LAB) as an important part of the gut community and their special beneficial activities for honeybee health. The idea of probiotics for honeybees as a promising tool to improve their health is widely discussed. Knowledge of the natural gut microbiota provides an opportunity to create a broad strategy for honeybee vitality, including the development of modern probiotic preparations to use instead of conventional antibiotics, environmentally friendly biocides, and biological control agents.